Inovação e competências: um estudo do processo de desenvolvimento de produtos na indústria automotiva - Mariana Drumond de Lima (2014)
In a corporate environment marked by the increase of dynamicity, innovation has become one of the most strategic priorities of organizations, extensively proven to be related to aboveaverage returns. Considering the phenomenon as part of a complex and cumulative social process that involves continuous efforts in creating knowledge, it is assumed that innovation related activities require not only individual involvement, but also a collective capacity that enables the organization to promote the coordination and the integration of individual knowledge and know-how. Given this perspective, this study aims to investigate theoretical and empirical evidence of the relationship between the construct of competence at the individual and organizational levels and the innovation process. A theoretical and methodological framework was developed with the purpose of evidencing how these relationships are discussed in the relevant literature. The framework was used to trace considerations about the empirical case, conducted in a subsidiary of the automotive sector, a historically significant segment for the Brazilian economy. Two specific cases regarding the organization were analyzed. The first case study covered the development of an electronic locker differential integrated to a front transversal transmission applied to off road vehicles. The other case involved the implementation of a corporate innovation program. Data analysis has allowed identifying evidences of relationships between the constructs, even though the competences dimension is not treated in a clearly and broadly way within the organization. Organizational strategies and their deployments in functional deliveries appear as key elements in the articulation between the constructs. The adopted strategic planning methodology proposes that the organizations strategy serves as input for the definition of the individual competencies necessary to accomplish the organizational objectives. The process is treated as a hierarchical flow that disregards the possibility of the emergence of strategies outside the formal planning methodology. In addition, the organization focuses on formal training programs that facilitate the transmission of explicit knowledge, without emphasizing actions that favor the development of tacit knowledge built through practical experiences. It is also noticed that, despite organization attempts to institutionalize its innovation processes, the participation in such activities is still restricted to a limited group of experts. As a conclusion, it is noticed that to create the conditions to build individual and organizational knowledge required for the success of innovation process, it is important that the organization invests in an appropriate structure, capable of providing autonomy and encourage internal communication processes, integration, exchange of experiences and collaboration among employees.